Development Of Team Games Tournament (Tgt) Model To Improve Learning Motivation In Students' Physical Learning At State Elementary School - Ulfani, Dhitia Putri; Neldi, Hendri; Syarastani, Syarastani; Welis, Wilda; Ockta, Yovhandra (STKIP Singkawang, 2024)
The problem in this study is that the PE (Physical Education) learning process still uses conventional learning models, due to the limitations of PE teachers in implementing various learning models, resulting in low student learning motivation. This study aims to produce a Team Games Tournament (TGT) model in PE learning to improve the learning motivation of students at Elementary School of 24 Bengkulu.This type of research is Research and Development (R&D) with the ADDIE development model, namely Analysis, Design, Development, Implementation, and Evaluation. The data obtained are assessments and suggestions from media experts, material experts and language experts, assessments and suggestions from PE teachers, self-assessment of student learning motivation. The analysis techniques used are validity tests, practicality tests and product effectiveness tests.The validation results show a very good level of validity, with 96.25% for media, 95.42% for material and 84.44% for language. The practicality test involving three PJOK teachers produced an average score of 98% indicating a very good level of practicality. The effectiveness test based on the results of N.Gain showed a percentage value of 81.94% with a very effective category. This shows that the Team Games Tournament (TGT) module can increase the learning motivation of class V students of Elementary School of 24 Bengkulu.